2014
DOI: 10.1055/s-0033-1363981
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates the Expression of the SHARP-1 Gene via Multiple Signaling Pathways

Abstract: The rat enhancer of split- and hairy-related protein-1 (SHARP-1) is a basic helix-loop-helix transcription factor. An issue of whether SHARP-1 is an insulin-inducible transcription factor was examined. Insulin rapidly increased the level of SHARP-1 mRNA both in vivo and in vitro. Then, signaling pathways involved with the increase of SHARP-1 mRNA by insulin were determined in H4IIE rat hepatoma cells. Pretreatments with LY294002, wortmannin, and staurosporine completely blocked the induction effect, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…12,13) Cell culture and treatments with insulin, various inhibitors, or adenoviruses were previously described. 6,7,10) Briefly, for analysis of a signaling pathway(s), 50 μM LY294002, 0.2 μM wortmannin, 0.1 μM staurosporine, 0.1 μM rapamycin, 25 μM PD98059, 10 nM okadaic acid, 10 μM JNK inhibitor II, 50 μM Rac1 inhibitor, 0.8 μM actinomycin D, or 10 μM cycloheximide were added to the medium at 15 min before the addition of 10 nM insulin. The adenovirus was infected with the 500 multiplicity of infection and cultured for an additional 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13) Cell culture and treatments with insulin, various inhibitors, or adenoviruses were previously described. 6,7,10) Briefly, for analysis of a signaling pathway(s), 50 μM LY294002, 0.2 μM wortmannin, 0.1 μM staurosporine, 0.1 μM rapamycin, 25 μM PD98059, 10 nM okadaic acid, 10 μM JNK inhibitor II, 50 μM Rac1 inhibitor, 0.8 μM actinomycin D, or 10 μM cycloheximide were added to the medium at 15 min before the addition of 10 nM insulin. The adenovirus was infected with the 500 multiplicity of infection and cultured for an additional 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Both a phosphoinositide 3-kinase (PI 3-K)/atypical protein kinase C lambda (aPKCλ)/Jun N-terminal kinase (JNK)-and a PI 3-K/ Rac/JNK-signaling pathway mediate an induction of the level of SHARP-1 mRNA by insulin. 6) However, that of SHARP-2 mRNA remains to be determined except for an involvement of PI 3-K. 4) Compounds that can induce both the SHARP-1 and SHARP-2 gene expression are useful for prevention and treatment of diabetes mellitus. We have reported that food constituents such as genistein, (-)-epigallocatechin-3-gallate (EGCG), and (S)-Equol, which lower blood glucose level in vivo, can stimulate these gene expression in H4IIE cells.…”
mentioning
confidence: 99%
“…Therefore, we hypothesize that SHARP-2 is an important transcription factor involving in the regulation of blood glucose levels (9,10). Recently, we have reported that SHARP-1, an isoform of SHARP-2, also involved in the regulation of gene expression by insulin (11).…”
Section: Thementioning
confidence: 99%
“…Recent studies have shown that insulin promotes the phosphorylation of the BMAL1 protein by Akt, thereby suppressing its transcriptional activity [ 103 ]. Furthermore, several studies demonstrated that insulin increases the expression levels of Per1 , Per2 , Dec1 , and Dec2 in cultured cells [ 104 , 105 , 106 , 107 ]. While the molecular mechanisms underlying insulin-induced expression of these clock genes remain to be elucidated, insulin signalling pathways may play an important role in the regulation of the molecular clock because insulin-induced expression of Dec1 and Dec2 was found to be inhibited by the blockade of phosphoinositide 3-kinase, protein kinase C, or mammalian target of rapamycin [ 104 , 105 , 106 ].…”
Section: Molecules At the Intersection Of The Molecular Clock And mentioning
confidence: 99%